Answer:
-y^4+4y
Step-by-step explanation:
Answer:
Graph 2.
Step-by-step explanation:
The graph is decreasing.
Hope this helps!
If not, I am sorry.
Here given,
and ![g(x) = x^2-9](https://tex.z-dn.net/?f=%20g%28x%29%20%3D%20x%5E2-9%20)
we have to find
which means the subtracting of the functions f(x) and g(x).
![(f-g)(x) = f(x) - g(x)](https://tex.z-dn.net/?f=%20%28f-g%29%28x%29%20%3D%20f%28x%29%20-%20g%28x%29%20%20)
= ![(3x^2+2) - (x^2-9)](https://tex.z-dn.net/?f=%20%283x%5E2%2B2%29%20-%20%28x%5E2-9%29%20)
= ![3x^2+2 -x^2-(-9)](https://tex.z-dn.net/?f=%203x%5E2%2B2%20-x%5E2-%28-9%29%20)
=
( we know that multiplication of negative and negative is positive)
= ![2x^2+2+9](https://tex.z-dn.net/?f=%202x%5E2%2B2%2B9%20)
=![2x^2+11](https://tex.z-dn.net/?f=%202x%5E2%2B11%20)
We have got the required answer here.
![(f-g)(x) = 2x^2+11](https://tex.z-dn.net/?f=%20%28f-g%29%28x%29%20%3D%202x%5E2%2B11%20)
<h3>
Answer: 15</h3>
=========================================================
Work Shown:
a = 9, b = 12 are the two legs of the right triangle
c = unknown is the hypotenuse
Apply the pythagorean theorem to find c
a^2 + b^2 = c^2
9^2 + 12^2 = c^2
81 + 144 = c^2
225 = c^2
c^2 = 225
c = sqrt(225)
c = 15
Answer:
10
Step-by-step explanation:
but not too for sure